1987
DOI: 10.2307/2336701
|View full text |Cite
|
Sign up to set email alerts
|

Rank Tests for Changepoint Problems

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Biometrika Trust is collaborating with JSTOR to digitize, preserve and extend access to Biometrika. SUMMARYWe consider procedures based on quadratic form rank statistics to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 4 publications
0
46
0
Order By: Relevance
“…Lombard [11] showed that the process defined by [28]. It is well-known that the W τ statistic and the M τ statistic are uncorrelated.…”
Section: A Location-scale Nonparametric Test Statisticmentioning
confidence: 99%
See 1 more Smart Citation
“…Lombard [11] showed that the process defined by [28]. It is well-known that the W τ statistic and the M τ statistic are uncorrelated.…”
Section: A Location-scale Nonparametric Test Statisticmentioning
confidence: 99%
“…Lombard [11] discussed procedures based on quadratic form rank statistics to test for one or more change points and derived the asymptotic distribution of the general linear rank statistics in the change-point problem. Aly and Abd-Rabou [12] discussed some rank test statistics assuming that the sample size is random by theoretically and via simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Tests constructed in Lombard [9] and Gombay [5] are based on rank statistics. Theorem 2 suggests tests based on the dyadic increments of empirical process.…”
Section: Testing Change Of Distribution Functionmentioning
confidence: 99%
“…To name only a few papers, see for example Bhattacharya and Brockwel (1976), Bhattacharya (1987), Bhattacharya and Frierson (1981), Carlstein (1988), Cs6rg6 and Horvhth (1987, 1988a, 1988b, Darkhovskh (1976), Deshayes and Picard (1981), Diimbgen (1991), Hinkley (1970), Lombard (1987), Lorden (1971), Page (1954Page ( , 1955, Pettitt (1979) or Siegmund (1988). Most of these papers have one feature in common: They do not investigate the power of the tests.…”
Section: Introductionmentioning
confidence: 99%